Efficacy of a general practitioner training campaign for early detection of melanoma in France3. (January 2014) - Grange, F.; Woronoff, A.S.; Bera, R.; Colomb, M.; Lavole, B.; Fournier, E.; Arnold, F.; Barbe, C.
Summary Background To date, no strategy for improving early diagnosis of melanoma has been evaluated on a population basis in France. Objective To evaluate the efficacy of a general practitioner (GP) awareness and training campaign in a pilot French geographical region (Champagne‐Ardenne), including 1·34 million inhabitants, 1241 GPs, 56 dermatologists and a population‐based melanoma registry. Methods All GPs received repeated awareness postal mailings in 2008 and 398 (32·1%) attended training sessions organized by 27 dermatologists. The pre‐ (2005–7) and post‐campaign (2009–11) periods were compared for the following: primary endpoint – the world‐standardized incidence of very thick melanomas (VTM) (Breslow thickness ≥ 3 mm); secondary endpoints – the mean Breslow thickness; the proportions of VTM and of thin (< 1 mm) melanomas among invasive cases; and the ratio of in situ/all melanoma cases. Similar measures were performed in the control area of Doubs/Belfort territory (655 000 ha), where no similar campaign was carried out. Results The incidence of VTM decreased from 1·07 to 0·71 per 100 000 habitants per year (P = 0·01), the mean Breslow thickness from 1·95 to 1·68 mm (P = 0·06) and the proportion of VTM from 19·2% to 12·8% (P = 0·01). The proportion of thin and in situ melanomas increased from 50·9% to 57·4% (P = 0·05) and from 20·1% to 28·2% (P = 0·001), respectively. No significant variation was observed in Doubs/Belfort territory. Conclusion These results strongly support the efficacy of such a campaign targeting GPs and provide a rationale for a larger public health campaign in France, including training of GPs by dermatologists and encouraging patients to ask their GP for a systematic skin examination.